Bioconversion of used potato cooking oil derived from palm oil into biodiesel and by-product glycerol / Nurshafiqa Burhanuddin - Burhanuddin, Nurshafiqa (Faculty of Plantation and Agrotechnology, 2018)
The increase of cooking oil uses and the awareness of the impact of pollution to the environment with increasing population has created a need to find an alternative on how to utilize the waste. The recovery of glycerol and biodiesel from the waste cooking oil can become an alternative in order to utilize the waste cooking oil. Glycerol is the principal by-product of biodiesel production. Some processes that have been developed in the process of biodiesel fuel production which transesterification using alkali-catalysis give high level of conversion of triglycerides to their corresponding methyl esters in short reaction times. There are countries that widely utilize biodiesel fuel production. In this research, enzymatic transesterification is used for biodiesel fuel production. It is because the glycerol produced as a by-product can be easily be recovered and the biodiesel are easily washed by distilled water. Based on the experiment, the amounts of glycerol for used and unused cooking oil are 3.75% as compared to 4%, and biodiesel produced are 75% and 80% respectively.